A new species of Malagasy blind snake of the genus Typhlops Oppel (Serpentes: Typhlopidae) - Renoult, Julien P.; Raselimanana, Achille P. (Zootaxa, 2009)
Madagascar is the third hottest biodiversity hotspot in the world with regard to the reptile fauna, after the Caribbean and middle-America (Myers et al. 2000). Moreover, 92% of the 365 described species are endemic to the island (Glaw & Vences 2007). Malagasy snakes of the family Typhlopidae are no exception to this pattern of endemism: except for the cosmopolitan, widespread and introduced Ramphotyphlops braminus (Daudin, 1803), all the other species of the family encountered in Madagascar are endemic to the island. The species are allocated into two genera: Xenotyphlops (endemic to Madagascar) and Typhlops (with a worldwide distribution). However, when contrasted with other tropical forests worldwide, and given the extraordinarily high rates of micro-endemism characterizing several reptile lineages on Madagascar (Yoder et al. 1995), the current species richness in Malagasy blind snakes is relatively low: only eight species are recognized in the genus Typhlops and two in Xenotyphlops (Glaw & Vences 2007). The opportunistic discovery of a Typhlops, that could not be assigned to any named taxon, close to a widely frequented research station of the eastern humid forest highlights the limited survey efforts in this region. The purpose of this paper is to describe this new taxon and to stress the need to increase field investigations in the eastern rain forest.